Development of CNT/SiO2 fillers reinforced polyester hybrid composites - Chong, Meng Mun (2015)
With the progress of time, emphasis on friction and wear of polymer matrix composites is increasingly important. Modest attempt has been made to develop hybrid polymer composites reinforced micro- and nano- sized fillers. Silica (SiO₂) and carboxylic functionalized multi-walled carbon nanotube (MWCNT-COOH) are favored in friction and wear properties were added into polyester resin. This widely used micro filler, SiO₂ were maintained at 10 wt. % while nano filler, MWCNT-COOH were at 0.1 wt. %, 0.3 wt. % and 0.8 wt. %. Prior to the fabrication, ultrasonicator was used to assist the dispersion of SiO₂ and MWCNT-COOHinto unsaturated polyester resin. Elimination of voids was optimized by evacuation of the mixture in vacuum drying oven. Vacuum infusion technique was established to produce pin samples and resin casting method were applied to fabricate samples in rectangle size. Improvement of light weight properties was proven by measurement of density of each ready sample using densitometer. Investigation towards the stiffness and resistance to abrasion of the hybrid composites were performed by Vickers Hardness Test. The samples with only carboxylic functionalized multi-walled carbon nanotube at different loadings were investigated on the dispersion state by utilizing Transmission Electron Microscope. As received SiO₂ and MWCNT-COOH as well as dispersion state of ready samples were observed using Field Emission Scanning Electron Microscope. Spectrums were recorded by Attenuated Total Reflectance Fourier Transform Infrared to identify the relevant bonding or structural changes which show interaction in between fillers and matrix material. Dynamic mechanical analysis was able to provide maximum service temperature, glass transition temperature and viscoelastic behavior of hybrid polyester composites prior to dry sliding test. Pin-on-disc testerwas used to reveal tribological properties of this material. Wear parameters were at sliding speeds of 1.6 m/s, 2.8 m/s and 4.0 m/s as well as applied loads of 5 N, 10 N and 20 N. Wear and friction process were investigated at sliding speed of 4.0 m/s and applied load of 20 N for 2 hours at sliding interval of 15 minutes. Observation of wear surfaces and wear particles has been made using scanning electron microscope. At the optimum loadings, UPR/SiO₂/0.8, agglomerates were observed which has led to further increase of specific wear rates. Interaction in between fillers and matrix had regulated the decrease in specific wear rate and coefficient of friction. Wear and friction of sample pins were protected by transfer film formed after dry sliding. Further sliding has led to detached of transfer or wear particles whether from wear surface of transfer film. Different types of wear particles were observed when types of fillers varied. Sharp and edges wear particles were found on sample with MWCNT-COOH added whereas rounded and least edges wear particles were found in sample with SiO₂ added. The development of this advanced material will give significant implications on application requiring light and low coefficient of friction.